Screen time and Sleep Quality among College and University Students of Karachi - Muhammad, Nizamuddin; Hussain, Mehwish; Adnan, Syed Muhammad (Journal of Health & Biological Sciences, 2021)
Objectives: To assess the relationship between screen times and sleep quality of the age group 17-24. Methodology: This is a cross-sectional study. The study was conducted on students of Colleges and universities in Gulshan-e-Iqbal Town Karachi. A total of 600 undergraduate students were approached in colleges and universities of Gulshan Town, Karachi. The sampling technique was Multi Staged sampling. The research instrument comprised of 3 parts i) Demographic profile, ii) Sleep quality measures and iii) Screen time usage measures. Results: The mean total hour of sleep was 6.7 ± 1.5. The Mean Cumulative score of the components of the questionnaire was 7.47 ± 3.56, while 174 (29%) have Normal Sleep quality and 426 (71%) have poor sleep according to the questionnaire. The odds ratio suggests there were 4.23 times higher chances of poor sleep quality in students whose screen time was more than 2 hours on weekdays as compared to other students. (OR: 4.23, 95% CI: 2.66-6.72). The odds ratio suggests there were 24.15 times higher chances of poor sleep quality in students whose screen time was more than 2 hours on weekends as compared to other students (OR: 24.15, 95% CI: 11.192-52.11). Conclusion: As, negative impacts were determined within sleep quality, and increased screen watching of multiple versions of the devices (screen time), influencing the commended level of screen watching among university and college students (age 17-24) is an affair of public health.